2014
DOI: 10.1371/journal.pone.0100814
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibitory Effect of Hyperbaric Oxygen Combined with Sorafenib on Hepatoma Cells

Abstract: ObjectivesHypoxia is a common phenomenon in solid tumors, associated with chemotherapy and radiotherapy resistance, recurrence and metastasis. Hyperbaric oxygen (HBO) therapy can increase tissue oxygen pressure and content to prevent the resistance, recurrence and metastasis of cancer. Presently, Sorafenib is a first-line drug, targeted for hepatocellular carcinoma (HCC) but effective in only a small portion of patients and can induce hypoxia. The purpose of this study is to investigate the effect of HBO in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The antiapoptotic Mcl-1 protein plays a critical role in the regulation of neutrophil apoptosis whereby decrease in intracellular protein levels usually correlate with increased apoptosis rate [ 34 ]. Previous studies postulated that HBO therapy provokes apoptosis in different cell types [ 35 – 37 ]. As depicted in Fig 5 , stimulation of cells with PMA triggered a strong decrease in intracellular Mcl-1 protein levels already after 4 h. However, this finding is particularly interesting as PMA was also found to increase the activity of p38 and ERK, the last one promoting Mcl-1 stabilization [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antiapoptotic Mcl-1 protein plays a critical role in the regulation of neutrophil apoptosis whereby decrease in intracellular protein levels usually correlate with increased apoptosis rate [ 34 ]. Previous studies postulated that HBO therapy provokes apoptosis in different cell types [ 35 – 37 ]. As depicted in Fig 5 , stimulation of cells with PMA triggered a strong decrease in intracellular Mcl-1 protein levels already after 4 h. However, this finding is particularly interesting as PMA was also found to increase the activity of p38 and ERK, the last one promoting Mcl-1 stabilization [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, hyperbaric oxygen combined with radiotherapy or chemotherapy has been intensively investigated 46 . An in vitro study showed that HBOT, sorafenib or cisplatin alone all could inhibit HCC cell growth, yet HBOT combined with sorafenib or cisplatin led to much greater synergistic proliferative inhibition and apoptotic induction 49 , suggesting a potential adjuvant application of HBOT in HCC patients.…”
Section: Hbot In Liver-related Cancermentioning
confidence: 99%
“…Some previous studies suggest that HBO therapy may improve postoperative outcome and outcome of radiotherapy and chemotherapy, especially proving beneficial for the treatment of radiotherapy (4,5). A combinatorial approach using chemotherapeutic drugs with HBO may enhance sensitivity of tumor cells to chemotherapeutic agents (6,7) and the application of HBO in chemotherapy for malignant lymphoma, brain tumor, lung cancer, gastric cancer and breast cancer may increase chemotherapeutic efficacy while decreasing treatment related toxicity (8). However, HBO treatment alone may stimulate the proliferation of tumor tissues (9).…”
Section: Introductionmentioning
confidence: 99%